Microvillus Inclusion Disease: Loss of Myosin Vb Disrupts Intracellular Traffic and Cell Polarity. (19th November 2013) - Thoeni, Cornelia E.; Vogel, Georg F.; Tancevski, Ivan; Geley, Stephan; Lechner, Silvia; Pfaller, Kristian; Hess, Michael W.; Müller, Thomas; Janecke, Andreas R.; Avitzur, Yaron; Muise, Aleixo; Cutz, Ernest; et al.
<x xml:space="preserve">Abstract</x> Missense and nonsense mutations in the MYO5B gene cause microvillus inclusion disease (MVID), a congenital enteropathy characterized by loss of apical microvilli and cytoplasmic microvillus inclusions. A non‐functional myosin Vb motor in mature enterocytes results in disorganized actin filaments, interruption of intracellular vesicle trafficking manifesting by redistributed Rab GTPases (Rab11, Rab9 and Rab8), mislocalized cell organelle markers (EEA1 and LAMP2) and transporter proteins (CD36, TfR and Na/K ATPase). This results in impaired intestinal barrier formation and severe loss of epithelial polarity. <boxed-text content-type="graphic" id="tra12131-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>